Differences in trends in the use of robot‐assisted and open radical cystectomy and changes over time in peri‐operative outcomes among selected centres in North America and Europe: an international multicentre collaboration. (2nd June 2019) - Zamboni, Stefania; Soria, Francesco; Mathieu, Romain; Xylinas, Evanguelos; Abufaraj, Mohammad; D`Andrea, David; Tan, Wei Shen; Kelly, John D.; Simone, Giuseppe; Gallucci, Michele; Meraney, Anoop; Krishna, Suprita; et al.
Abstract : Objectives: To compare trends in the use of robot‐assisted radical cystectomy (RARC) and changes over time in peri‐operative outcomes in selected North American and European centres. Materials and Methods: We conducted a retrospective evaluation of 2401 patients treated with open radical cystectomy (ORC) or RARC for bladder cancer at 12 centres in North America and Europe between 2006 and 2018. We used the Kruskal–Wallis and chi‐squared test to evaluate differences between continuous and categorical variables. Results: Overall, 49.5% of patients underwent RARC and 51.5% ORC. RARC became the most commonly performed procedure in contemporary patients, with an increase from 29% in 2006–2008 to 54% in 2015–2018 ( P < 0.001). In the North American centres the use of RARC was higher than that of ORC from 2006, and remained stable over time, whereas in the European centres its use increased exponentially from 2% to 50%. In both groups patients who underwent RARC had less advanced T stages ( P < 0.001), lower American Society of Anesthesiologists scores ( P < 0.05), lower blood loss ( P = 0.001) and shorter length of hospital stay ( P < 0.05). No differences were found in early complications. Early readmission and re‐operation rates were worse for patients treated with RARC in the European centres; however, when contemporary patients only were considered, the statistical significance was lost. Conclusion: The present study shows that the use of RARC has constantly increased since its introduction, overtaking ORC in the most contemporary series. While RARC was more frequently performed than ORC since its introduction in the North American centres and its use remained substantially stable over time, its use increased exponentially in the European centres. The different trends in use of RARC/ORC and changes over time in peri‐operative outcomes between the North American and European centres can be attributed to the earlier introduction and spread of RARC in the former compared with the latter.